Causal effects of gut microbiota on diabetic retinopathy: A Mendelian randomization study - Liu, Kangcheng; Zou, Jing; Fan, Huimin; Hu, Hanying; You, Zhipeng (Frontiers in Immunology, 2022)
Background: Previous researches have implicated a vital association between gut microbiota (GM) and diabetic retinopathy (DR) based on the association of the “gut-retina” axis. But their causal relationship has not been elucidated. Methods: Instrumental variables of 211 GM taxa were obtained from genome wide association study (GWAS), and Mendelian randomization study was carried out to estimate their effects on DR risk from FinnGen GWAS (14,584 DR cases and 202,082 controls). Inverse variance weighted (IVW) is the main method to analyze causality, and MR results are verified by several sensitive analyses. Results: As for 211 GM taxa, IVW results confirmed that family-Christensenellaceae (P = 1.36×10-2) and family-Peptococcaceae (P = 3.13×10-2) were protective factors for DR. Genus-Ruminococcaceae_UCG_011 (P = 4.83×10-3), genus-Eubacterium_rectale_group (P = 3.44×10-2) and genus-Adlercreutzia (P = 4.82×10-2) were correlated with the risk of DR. At the phylum, class and order levels, we found no GM taxa that were causally related to DR (P>0.05). Heterogeneity (P>0.05) and pleiotropy (P>0.05) analysis confirmed the robustness of MR results. Conclusion: We confirmed that there was a potential causal relationship between some GM taxa and DR, which highlights the association of the "gut-retina" axis and offered new insights into the GM-mediated mechanism of DR. Further explorations of their association are required and will lead to find new biomarkers for targeted prevention strategies of DR.